The interaction of crime & place: an exploratory study of crime & policing in non-metropolitan areas - Shukla, Rashi K. (Crime prevention and community safety, 2019)
The importance of crime and place and the diversity inherent in crime problems and policing styles have been recognized for decades. However, less is known about the types of issues and challenges that must be confronted by agencies located in rural communities. This exploratory research presents preliminary findings from a study of six non-metropolitan law enforcement agencies nested within rural areas in Oklahoma. Qualitative interviews and field visits were conducted with a purposive sample of departmental officials. Data collection efforts focused on understanding the types of issues the departments face and the current state of the drug and crime problems in these areas. Key themes include law enforcement challenges, crime, drugs, and gang activity. Unanticipated findings that emerged during the course of the research are also discussed.